SYSTEMATIC LITERATURE REVIEW: EFEK LATIHAN FISIK TERHADAP FUNGSI KOGNITIF LANSIA - Rauf, Saidah; Kaimuddin, Riski Amalia; Olla, Marice Benga (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2023)
Background: Cognitive decline is a common problem among the elderly. Cognitive disorders can be treated with an active lifestyle that includes regular physical activity. Objective: This study aims to examine the effect of physical exercise on the cognitive function of the elderly. Methods: The current study is a systematic review of published research articles using a Randomized Control Trial and a quasi-experimental design. The Garuda Portal and Pubmed databases were consulted for document identification. The articles were published between 2018 and 2021 in peer-reviewed journals and include respondents aged 45 years. No OR Control AND Gym OR Exercise AND Cognitive OR Memory AND Elderly OR Aging OR Elder were the keywords used for Pubmed searching. The keywords for portal garuda were Pengaruh DAN Latihan Fisik DAN Kognitif DAN Lansia. Results: The first stage of indentification were found 575 articles which fit to the keywords. After following the Prisma ways, a numbers of 9 articles were chosed for review. Exercise has been shown to improve cognitive function in every article reviewed. Aerobic and neuromuscular exercises are typically used. Conclusion: Physical exercise can help the elderly improve their cognitive function.